MARKET TRENDS AND CHALLENGES FOR THE FRESH FRUIT TRADE - N. Petrova (Trakia Journal of Sciences)
The natural and climatic conditions in Bulgaria are a prerequisite for the cultivation of quality fruits with unique taste characteristics, but after the country's accession to the EU, there is a permanent tendency to decrease the areas on which fruit crops are grown. The consumption of fresh fruits and vegetables in developed and developing countries is far below the recommended norms, and yet production in the country cannot satisfy the needs of the population with fresh fruits and the canning industry with raw materials. The purpose of this paper is to analyze the characteristics of the fruit market in Bulgaria.